The Analysis of Productivity at PT. Perkebunan Nusantara IV Unit Teh Bah Butong - Syarifah Akmal; Syarifah Yusra (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
PT. Perkebunan Nusantara IV Teh Bah Butong Business Unit, a company that produces products in the form of powdered tea, is one of the companies that continues to grow. Based on observations made in the production processing section, the tea production process often experiences problems. One of the causes is the declining performance of the factors of production, namely equipment. This declining performance of production factors is the cause of the loss of productive time within a certain time. Economically, this would be counter-productive to efforts to meet the company's production targets. This problem will be analyzed by measuring the overall effectiveness of production factors or machines (OEE method), as an important part of a series of industrial production processes. From the calculation results, the level of effectiveness of the production system performance according to world-class benchmark standards has not yet reached the specified standard. In measuring effectiveness, the average performance is 67%. This figure can actually be increased, so that it shows the production performance as targeted by the corporation.